The Leading Sector for West Sumatera in Facing the ASEAN Economic Community - Rosra, Deswita (KnE Social Sciences, 2022)
This paper aimed to determine the leading sectors in working with the ASEAN Economic Community (AEC) in West Sumatra. These sectors support regional readiness in facing the AEC. This study used a normative legal method, with secondary data consisting of primary, secondary and tertiary legal materials. Data were analyzed qualitatively. The results showed that Indonesia has 12 priority sectors in the trade of goods and services that can be favored in facing the AEC, while the West Sumatra region has three such sectors. The West Sumatra region must be able to optimally utilize these sectors to work with the AEC. The region must prepare for regional competitiveness from various angles, because competitiveness is the key to success or failure in utilizing the AEC. Keywords: sector, leading, facing, AEC